Role of home-based pulmonary rehabilitation programs for disease progression and quality of life in patients with stable bronchiectasis: a single-center RCT - Siwen Min; Hongting Liu; Yajuan Zhang; Jingyi Wang; Li Wang; Yifan Jiang; Suxia Shi (Frontiers in Medicine)
ObjectiveThis study aims to evaluate the effectiveness of a home-based pulmonary rehabilitation program for patients with stable bronchiectasis in improving their quality of life and reducing acute exacerbations.MethodsA randomized controlled trial design was employed, with patients randomly assigned to an intervention group (receiving the pre-designed home-based pulmonary rehabilitation program for bronchiectasis) or a control group (receiving standard respiratory care). The effects of the program on quality of life, lung function indicators, and the frequency of acute exacerbations were assessed.ResultsPreliminary findings indicate that the home-based pulmonary rehabilitation program significantly improved quality of life scores, enhanced lung function, and reduced the frequency of acute exacerbations (p < 0.05).ConclusionThe home-based pulmonary rehabilitation program is an effective intervention for patients with stable bronchiectasis, contributing to improved clinical outcomes and quality of life.